2002
DOI: 10.1051/0004-6361:20021244
|View full text |Cite
|
Sign up to set email alerts
|

Solar activity cycle and rotation of the corona

Abstract: Abstract. In this paper we consider the dependence of the coronal rotation period on solar activity. We analyzed the 10.7 cm radio emission flux covering cycles 19 to 22. We have established a new method for studying the rotation rate: by identifying the flux pulses with the recurrence of active longitudes. We first determined the frequency domain of the rotation and then analyzed each cycle separately. The entire domain of 51.7 years was divided into 480-day sections, which were analyzed independently and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Mouradian et al (2002) show that the number of peaks of the power spectrum grows in accordance with cycle evolution. The changes of RR during the cycle are not systematic, as the differential rotation rule can suggest.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Mouradian et al (2002) show that the number of peaks of the power spectrum grows in accordance with cycle evolution. The changes of RR during the cycle are not systematic, as the differential rotation rule can suggest.…”
Section: Discussionmentioning
confidence: 82%
“…To reveal the fluctuations the smooth function is subtracted from the recordings in order to point out an alternate function around a straight line. This is the clear slow varying component of solar activity, that will be treated by harmonic analysis (Mouradian et al 2002). For each considered time interval, the position of the straight line was corrected to obtain the sum of alternate functions equal to zero.…”
Section: Methods Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To compare with the stellar behavior, I prefer to use an integral measure of the solar activity. Such a measure with an extended time base is the radio flux at 10.7 cm which has been investigated by Mouradian et al (2002) who found many peaks in the power spectrum between 25 and 29 days. Another measure that reveals the activity in the photospheric layers of the Sun is the daily sunspot number.…”
Section: Introductionmentioning
confidence: 99%